Molybdenum cobalt nitride Co3Mo3N and preparation method thereof
By using molybdenum cobalt nitride Co3Mo3N as the positive electrode material in Li-CO2 batteries, using nitrogen-containing compounds and cobalt atom doping technology, the problem of slow decomposition kinetics and insufficient safety and environmental protection of Li2CO3 is solved, and high-efficiency CO2RR and low-efficiency Catalytic effect of potential.
Patent Information
- Application Number
- CN202411783941.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-07
AI Technical Summary
Li-CO2 batteries have application prospects in high energy density storage and efficient CO2 fixation, but the decomposition kinetics of its reducing product Li2CO3 are slow, resulting in high overpotentials and poor rechargeability. The existing transition metal nitride synthesis methods are safe and environmentally friendly. insufficient.
Using nitrogen-containing compounds as nitrogen source, nanocomposite materials are prepared under the protection of nitrogen and other atmospheres during heat treatment. The electronic structure of molybdenum nitride is modulated through transition metal cobalt atom doping engineering technology, and the molybdenum cobalt nitride Co3Mo3N is prepared as lithium carbon dioxide battery. The positive electrode material improves its conductivity and CO2 adsorption energy.
The low overpotential and excellent cyclic stability of the molybdenum cobalt nitride Co3Mo3N were achieved, which significantly improved the dynamic characteristics of CO2RR, reduced the charging voltage platform, and significantly improved the catalytic effect.
Smart Images

Figure CN119263358A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical energy, and in particular to a molybdenum-cobalt nitride Co3Mo3N and a preparation method thereof. Background Art
[0002] Non-precious metal catalysts such as transition metal phosphides, sulfides, and nitrides have been widely studied to replace precious metals due to their low cost and stability. Among them, transition metal nitrides have also received widespread attention due to their excellent catalytic performance. By introducing nitrogen atoms into transition metals to increase the d electron density, the electronic structure of transition metal nitrides is then made similar to that of precious metals, such as Pd and Pt. At present, the common synthesis routes of transition metal nitrides are nitridation of transition metal oxides, ammonolysis of metal chlorides, and decomposition of amine-containing polymer precursors. However, transition metal nitrides are generally synthesized at high temperatures using ammonia as a nitrogen source. Therefore, it is of great significance to accelerate the preparation technology of metal nitrides using safe and environmentally friendly methods.
[0003] Li-CO2 batteries have broad application prospects in high energy density storage and efficient CO2 fixation. However, the decomposition kinetics of Li2CO3, the reduction product of Li-CO2 batteries, is slow, resulting in high overpotential and poor rechargeability. In Li-CO2 batteries, molybdenum nitride as a catalyst has a high adsorption energy for CO2 and can accelerate the decomposition of Li2CO3. On this basis, the present invention uses transition metal cobalt atom doping engineering technology to modulate the electronic structure of molybdenum nitride, and prepares molybdenum cobalt nitride catalysts for use as positive electrode materials for lithium carbon dioxide batteries to obtain higher electrical conductivity and adsorption energy for CO2, which is beneficial to CO2RR kinetics. Summary of the invention
[0004] The present invention uses nitrogen-containing compounds as nitrogen sources, and uses nitrogen or other atmospheres to protect the heat treatment process to prepare nanocomposites, thereby improving the synthesis efficiency of metal nitrides, avoiding the use of NH3, and making the material preparation process safer, greener, and more efficient. The prepared monometallic nitride or bimetallic nitride is used as a positive electrode catalytic material for lithium carbon dioxide batteries, and has great application potential. The present invention provides a new method for synthesizing metal nitrides, and uses the same as a positive electrode catalyst for lithium carbon dioxide batteries. The prepared Co3Mo3N composite material has high adsorption energy for carbon dioxide and excellent ability to catalyze the decomposition of discharge products. When used as a positive electrode catalyst in lithium carbon dioxide batteries, it exhibits low overpotential and excellent cycle stability.
[0005] The present invention provides a molybdenum-cobalt nitride and a preparation method thereof, comprising the following steps: Step (1), synthesis of a nanorod-shaped cobalt molybdate precursor: a cobalt salt and a molybdenum salt in a certain molar ratio are mixed and dissolved in deionized water, and one of cetyltrimethylammonium bromide, urea or polyoxyethylene polyoxypropylene ether is added, and the mixture is stirred evenly and then transferred to a polytetrafluoroethylene reactor for microwave irradiation reaction. After the solution is cooled naturally, the mixture is washed with water and ethanol, and then centrifuged to obtain a product, which is then dried and pre-sintered to obtain a nanocrystalline cobalt molybdate precursor; Step (2), synthesis of bimetallic molybdenum-cobalt nitride with dual-effect catalytic effect: the obtained precursor and the nitrogen-containing compound are loaded into a porcelain boat according to a certain mass ratio, placed in a tubular furnace protected by an inert atmosphere, heated at a certain heating rate and kept warm for a certain time, and naturally cooled to room temperature to obtain the molybdenum-cobalt nitride positive electrode material.
[0006] Further, in step (1), the cobalt salt is one or a mixture of ethylenediaminetetraacetic acid disodium cobalt salt, 4-cyclohexylbutyric acid cobalt salt, cobalt chloride, cobalt (III) acetylacetonate, hexamidocobalt (III) chloride, cobalt (II) fluoride or cobalt nitrate hexahydrate, and the mixing ratio is 1:9 to 9:1; the molybdenum salt is one or a mixture of molybdenum (II) acetate dimer, bis (tert-butylimide) bis (dimethylamino) molybdenum (VI), trichloroisopropanol molybdenum (V), sodium molybdate dihydrate or ammonium molybdate heptahydrate, and the mixing ratio is 1:9 to 9:1.
[0007] Furthermore, in step (1), the molar ratio of the cobalt salt and the molybdenum salt in a certain molar ratio is 1:1-4:1, the stirring time is 0.5-2 hours, the microwave irradiation reaction uses a power range of 50-300 W, the reaction time is from 5 to 60 minutes, and the microwave reaction temperature is 100-200°C.
[0008] Furthermore, in step (1), the centrifugal speed is 4000-10000 rpm, the time is 3-10 min, the drying temperature after centrifugation is 60-100° C., and the drying time is 12-24 hours; the product is sintered in a tubular furnace, the heating rate of the tubular furnace is 5-10° C. / min, the maximum temperature is 300-500° C., and the heating time is 2-3 hours.
[0009] Furthermore, the nitrogen-containing compound in step (2) is polypyrrole, melamine or urea; and the mass ratio of the precursor to the nitrogen-containing compound is 1:1 to 1:10.
[0010] Furthermore, the inert atmosphere in step (2) is one or more of nitrogen, helium, argon or argon-hydrogen mixture; the heating rate of the tubular furnace is 2-10°C / min, the calcination temperature is 400-1000°C, and the calcination time is 1-6 hours.
[0011] The present invention provides molybdenum-cobalt nitride prepared by the above method.
[0012] The present invention also provides a lithium carbon dioxide battery, characterized in that the molybdenum cobalt nitride Co3Mo3N is mixed with a conductive agent and a binder in proportion, uniformly dispersed in NMP or isopropanol, and a conductive carbon paper is used as a current collector to prepare a positive electrode of the lithium carbon dioxide battery; metallic lithium is used as a negative electrode and a reference electrode; and the electrolyte is prepared by dissolving a lithium salt in an organic solvent.
[0013] Furthermore, the conductive agent used is one of superconductive carbon black, single-walled carbon nanotubes and multi-walled carbon nanotubes; the binder used is polyvinylidene fluoride or Nafion; the lithium salt concentration is 1 M~1.2 M, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium dioxalate borate or lithium difluorooxalate borate, and the solvent used is tetraethylene glycol dimethyl ether or dimethyl sulfoxide.
[0014] The invention provides an application of molybdenum cobalt nitride Co3Mo3N in a lithium carbon dioxide battery. Beneficial Effects
[0015] 1. During the heat treatment process, by mixing the nitrogen-containing compound with the precursor, at a certain temperature, ammonia is generated as a nitrogen source to nitride the composite material and generate molybdenum-cobalt nitride, which is safer and more environmentally friendly than directly using ammonia to react.
[0016] 2. The electronic structure of molybdenum nitride was modulated by transition metal cobalt atom doping engineering technology to obtain higher conductivity and adsorption energy for CO2, which is beneficial to improve the kinetic characteristics of electrochemical reduction of CO2 (CO2RR).
[0017] 3. The molybdenum-cobalt-nitride composite material of the present invention is used as a positive electrode catalyst for a lithium carbon dioxide battery, which can efficiently catalyze the electrochemical reduction reaction of CO2 and its reverse reaction, effectively alleviate the positive electrode polarization of the lithium carbon dioxide battery, reduce the charging voltage platform, and increase the discharge voltage platform, with a significant catalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the X-ray diffraction pattern of the molybdenum cobalt nitride Co3Mo3N prepared in Example 7.
[0019] Figure 2 The molybdenum cobalt nitride Co3Mo3N prepared in Example 7 was heated to 100 mAg -1 Constant capacity charge and discharge at current density up to 1000 mAhg -1 The first charge and discharge curve of the next cycle performance. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with the accompanying drawings and embodiments: Example 1 Disodium cobalt salt of ethylenediaminetetraacetic acid and molybdenum (II) acetate dimer were dissolved in 60 mL of deionized water at a molar ratio of 1:1 and hexadecyltrimethylammonium bromide was added, stirred for 30 min, transferred to a 100 mL reactor, reacted for 10 min at a microwave power of 100 W, and after the solution was naturally cooled, washed with water and ethanol 3 times each, then centrifuged to obtain the product, which was dried at 60 ° C. The product was sintered in a tubular furnace at a temperature of 300 ° C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0021] The precursor CoMoO4 and melamine were mixed in a mass ratio of 1:3, sintered at 800 °C for 3 h in an Ar atmosphere, with a heating rate of 5 °C / min, and cooled naturally to room temperature. Molybdenum cobalt nitride Co3Mo3N was obtained. The above powder Co3Mo3N was mixed with superconducting carbon black and PVDF in a mass ratio of 8:1:1, and then an appropriate amount of NMP solvent was added and ground to form a slurry. The slurry was poured on carbon paper and evenly coated with a scraper, and then dried in a vacuum oven to prepare an electrode sheet.
[0022] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1 M LiTFSI dissolved in TEGDME solution was used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0023] Example 2 Disodium cobalt salt of ethylenediaminetetraacetic acid and molybdenum (II) acetate dimer were dissolved in 60 mL of deionized water at a molar ratio of 1:2 and hexadecyltrimethylammonium bromide was added, stirred for 30 min, transferred to a 100 mL reactor, reacted for 30 min at a microwave power of 100 W, and after the solution was cooled naturally, washed with water and ethanol 3 times each, then centrifuged to obtain the product, and dried at 60 ° C. The product was sintered in a tubular furnace at a temperature of 300 ° C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0024] The precursor CoMoO4 and melamine were mixed in a mass ratio of 1:5, sintered at 700 °C for 4 h in a He atmosphere with a heating rate of 5 °C / min, and cooled naturally to room temperature to obtain molybdenum cobalt nitride Co3Mo3N.
[0025] The above powder Co3Mo3N was mixed with superconducting carbon black and PVDF in a mass ratio of 8:1:1, and then a proper amount of NMP solvent was added and ground into a slurry. The slurry was poured onto carbon paper and evenly coated with a scraper, and then dried in a vacuum oven to prepare an electrode sheet.
[0026] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1 M LiFSI and 0.2 M LiNO3 dissolved in DMSO solution were used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0027] Example 3 4-cyclohexylbutyric acid cobalt salt and molybdenum (II) acetate dimer were dissolved in 60 mL of deionized water at a molar ratio of 1:5 and hexadecyltrimethylammonium bromide was added, stirred for 30 min, transferred to a 100 mL reactor, reacted at a microwave power of 100 W for 50 min, and after the solution was naturally cooled, washed with water and ethanol 3 times each, then centrifuged to obtain the product, and dried at 60°C. The product was sintered in a tubular furnace at a temperature of 400°C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0028] The precursor CoMoO4 and urea were mixed in a mass ratio of 1:1, sintered at 900 °C for 2 h in an Ar atmosphere, with a heating rate of 10 °C / min, and cooled naturally to room temperature. Molybdenum cobalt nitride was obtained. The above powder Co3Mo3N was mixed with superconducting carbon black and PVDF in a mass ratio of 7:2:1, and then an appropriate amount of NMP solvent was added and ground to form a slurry. The slurry was poured on carbon paper and evenly coated with a scraper, and then dried in a vacuum oven to prepare an electrode sheet.
[0029] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1.2 M LiTFSI dissolved in DMSO solution was used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0030] Example 4 Cobalt chloride and bis(tert-butylimide)bis(dimethylamino)molybdenum(VI) were dissolved in 60 mL of deionized water at a molar ratio of 1:9 and polyoxyethylene polyoxypropylene ether was added, stirred for 30 min, transferred to a 100 mL reactor, reacted at a microwave power of 150 W for 10 min, and after the solution was naturally cooled, washed with water and ethanol 3 times each, then centrifuged to obtain the product, which was dried at 60 ° C. The product was sintered in a tubular furnace at a temperature of 450 ° C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0031] The precursor CoMoO4 and urea were mixed in a mass ratio of 1:5, sintered at 800 °C for 2 h in a N2 atmosphere, with a heating rate of 5 °C / min, and cooled naturally to room temperature. Molybdenum cobalt nitride was obtained. The above powder Co3Mo3N was mixed with carbon nanotube conductive glue in a mass ratio of 7:3, and then 50 μL Nafion binder and 950 μL isopropanol solvent were added to form a slurry after ultrasonic treatment. A certain volume of slurry was drawn with a pipette and dripped on a circular carbon paper with a diameter of 12 mm, and then placed in a vacuum oven for drying to prepare an electrode sheet.
[0032] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1 M LiDFOB dissolved in DMSO solution was used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0033] Example 5 Cobalt chloride and molybdenum (II) acetate dimer were dissolved in 60 mL of deionized water at a molar ratio of 9:1 and polyoxyethylene polyoxypropylene ether was added, stirred for 30 min, transferred to a 100 mL reactor, reacted at a microwave power of 150 W for 30 min, and after the solution was naturally cooled, washed with water and ethanol 3 times each, then centrifuged to obtain the product, and dried at 60 ° C. The product was sintered in a tubular furnace at a temperature of 450 ° C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0034] The precursor CoMoO4 and urea were mixed in a mass ratio of 1:5, sintered at 500 °C for 5 h in an Ar atmosphere, with a heating rate of 5 °C / min, and cooled naturally to room temperature. Molybdenum cobalt nitride was obtained. The above powder Co3Mo3N was mixed with carbon nanotube conductive glue in a mass ratio of 8:1, and then 50 μL Nafion binder and 950 μL isopropanol solvent were added to form a slurry after ultrasonic treatment. A certain volume of slurry was drawn with a pipette and dripped on a circular carbon paper with a diameter of 12 mm, and then placed in a vacuum oven for drying to prepare an electrode sheet.
[0035] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1.1 M LiTFSI dissolved in TEGDME solution was used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0036] Example 6 Cobalt chloride and molybdenum (II) acetate dimer were dissolved in 60 mL of deionized water at a molar ratio of 4:1 and urea was added, stirred for 30 min, transferred to a 100 mL reactor, reacted at a microwave power of 150 W for 50 min, and after the solution was cooled naturally, washed with water and ethanol three times each, then centrifuged to obtain the product, and dried at 60 ° C. The product was sintered in a tubular furnace at a temperature of 450 ° C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0037] The precursor CoMoO4 and polypyrrole were mixed in a mass ratio of 1:2, sintered at 900 °C for 2 h in a N2 atmosphere, with a heating rate of 10 °C / min, and cooled naturally to room temperature. Molybdenum cobalt nitride was obtained. The above powder Co3Mo3N was mixed with superconducting carbon black and PVDF in a mass ratio of 8:1:1, and then an appropriate amount of NMP solvent was added and ground to form a slurry. The slurry was poured on carbon paper and evenly coated with a scraper, and then dried in a vacuum oven to prepare an electrode sheet.
[0038] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1.1 M LiFSI and 0.3 M LiNO3 dissolved in DMSO solution were used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0039] Example 7 Cobalt nitrate hexahydrate and sodium molybdate dihydrate were dissolved in 60 mL of deionized water at a molar ratio of 1:1 and urea was added, stirred for 30 min, transferred to a 100 mL reactor, reacted for 30 min at a microwave power of 200 W, and after the solution was naturally cooled, washed with water and ethanol 3 times each, then centrifuged to obtain a product, which was dried at 60 ° C. The product was sintered in a tubular furnace at a temperature of 450 ° C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0040] The precursor CoMoO4 and polypyrrole were mixed in a mass ratio of 1:1, sintered at 900 °C for 2 h in a N2 atmosphere, with a heating rate of 10 °C / min, and cooled naturally to room temperature. Molybdenum cobalt nitride was obtained. The above powder Co3Mo3N was mixed with carbon nanotube conductive glue in a mass ratio of 8:2, and then 50 μL Nafion binder and 950 μL isopropanol solvent were added to form a slurry after ultrasonic treatment. A certain volume of slurry was drawn with a pipette and dripped on a circular carbon paper with a diameter of 12 mm, and then placed in a vacuum oven for drying to prepare an electrode sheet.
[0041] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1 M LITFSI and 0.3 M LiNO3 dissolved in DMSO solution were used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0042] Figure 1 The X-ray diffraction pattern of the molybdenum cobalt nitride Co3Mo3N prepared in Example 7 is shown, and the prepared material is completely consistent with the characteristic diffraction peak in the XRD standard card of Co3Mo3N; The electrochemical performance test of the battery of Example 7 was carried out. Figure 2 The molybdenum cobalt nitride Co3Mo3N prepared in Example 7 was heated to 100 mAg -1 Constant capacity charge and discharge at current density up to 1000 mAhg -1 The first charge and discharge curve of the lower cycle performance shows that the minimum polarization voltage is 1.39 V; Example 8 Cobalt nitrate hexahydrate and sodium molybdate dihydrate were dissolved in 60 mL of deionized water at a molar ratio of 2:1 and polyoxyethylene polyoxypropylene ether was added, stirred for 30 min, transferred to a 100 mL reactor, reacted at a microwave power of 200 W for 10 min, and after the solution was naturally cooled, washed with water and ethanol 3 times each, then centrifuged to obtain the product, and dried at 60 ° C. The product was sintered in a tubular furnace at a temperature of 450 ° C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0043] The precursor CoMoO4 and polypyrrole were mixed in a mass ratio of 1:10, sintered at 800 °C for 2 h in a N2 atmosphere, with a heating rate of 5 °C / min, and cooled naturally to room temperature. Molybdenum cobalt nitride was obtained. The above powder Co3Mo3N was mixed with carbon nanotube conductive glue in a mass ratio of 7:3, and then 50 μL Nafion binder and 950 μL isopropanol solvent were added to form a slurry after ultrasonic treatment. A certain volume of slurry was drawn with a pipette and dripped on a circular carbon paper with a diameter of 12 mm, and then placed in a vacuum oven for drying to prepare an electrode sheet.
[0044] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1 M LiFSI and 0.3 M LiNO3 dissolved in DMSO solution were used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0045] Example 9 Cobalt nitrate hexahydrate and ammonium molybdate heptahydrate were dissolved in 60 mL of deionized water at a molar ratio of 1:2 and polyoxyethylene polyoxypropylene ether was added, stirred for 30 min, transferred to a 100 mL reactor, reacted at a microwave power of 200 W for 50 min, and after the solution was naturally cooled, washed with water and ethanol 3 times each, then centrifuged to obtain the product, and dried at 60 ° C. The product was sintered in a tubular furnace at a temperature of 450 ° C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0046] The precursor CoMoO4 and melamine were mixed in a mass ratio of 1:5, sintered at 700 °C for 2 h in a N2 atmosphere, with a heating rate of 10 °C / min, and cooled naturally to room temperature. Molybdenum cobalt nitride was obtained. The above powder Co3Mo3N was mixed with carbon nanotube conductive glue in a mass ratio of 7:3, and then 50μL Nafion binder and 950μL isopropanol solvent were added to form a slurry after ultrasonic treatment. A certain volume of slurry was drawn with a pipette and dripped on a circular carbon paper with a diameter of 12 mm, and then placed in a vacuum oven for drying to prepare an electrode sheet.
[0047] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1 M LiBOB and 0.3 M LiNO3 dissolved in TEGDME solution were used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0048] Example 10 Cobalt nitrate hexahydrate and sodium molybdate dihydrate were dissolved in 60 mL of deionized water in a molar ratio of 1:1, and hexadecyltrimethylammonium bromide was added, stirred for 30 min, transferred to a 100 mL reactor, and reacted for 10 min at a microwave power of 250 W. After the solution was cooled naturally, it was washed with water and ethanol three times each, then centrifuged to obtain a product, and dried at 60 ° C. The product was sintered in a tubular furnace at a temperature of 500 ° C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0049] The precursor CoMoO4 and melamine were mixed in a mass ratio of 1:2, sintered at 900 °C for 2 h in a N2 atmosphere, with a heating rate of 10 °C / min, and cooled naturally to room temperature. Molybdenum cobalt nitride was obtained. The above powder Co3Mo3N was mixed with carbon nanotube conductive glue in a mass ratio of 7:3, and then 50μL Nafion binder and 950μL isopropanol solvent were added to form a slurry after ultrasonic treatment. A certain volume of slurry was drawn with a pipette and dripped on a circular carbon paper with a diameter of 12 mm, and then placed in a vacuum oven for drying to prepare an electrode sheet.
[0050] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1 M LiBOB dissolved in DMSO solution was used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0051] Example 11 Cobalt nitrate hexahydrate and ammonium molybdate heptahydrate were dissolved in 60 mL of deionized water at a molar ratio of 1:2 and urea was added, stirred for 30 min, transferred to a 100 mL reactor, reacted for 30 min at a microwave power of 250 W, and after the solution was naturally cooled, washed with water and ethanol 3 times each, then centrifuged to obtain a product, which was dried at 60 ° C. The product was sintered in a tubular furnace at a temperature of 500 ° C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0052] The precursor CoMoO4 and melamine were mixed in a mass ratio of 1:1, sintered at 600 °C for 2 h in a N2 atmosphere, with a heating rate of 5 °C / min, and cooled naturally to room temperature. Molybdenum cobalt nitride was obtained. The above powder Co3Mo3N was mixed with carbon nanotube conductive glue in a mass ratio of 7:3, and then 50 μL Nafion binder and 950 μL isopropanol solvent were added to form a slurry after ultrasonic treatment. A certain volume of slurry was drawn with a pipette and dripped on a circular carbon paper with a diameter of 12 mm, and then placed in a vacuum oven for drying to prepare an electrode sheet.
[0053] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1 M LiBOB dissolved in DMSO solution was used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0054] Example 12 Cobalt nitrate hexahydrate and ammonium molybdate heptahydrate were dissolved in 60 mL of deionized water at a molar ratio of 1:2 and polyoxyethylene polyoxypropylene ether was added, stirred for 30 min, transferred to a 100 mL reactor, reacted at a microwave power of 250 W for 50 min, and after the solution was naturally cooled, washed with water and ethanol 3 times each, then centrifuged to obtain a product, which was dried at 60 ° C. The product was sintered in a tubular furnace at a temperature of 500 ° C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0055] The precursor CoMoO4 and urea were mixed in a mass ratio of 1:1, sintered at 400 °C for 2 h in a N2 atmosphere, with a heating rate of 5 °C / min, and cooled naturally to room temperature. Molybdenum cobalt nitride was obtained. The above powder Co3Mo3N was mixed with carbon nanotube conductive glue in a mass ratio of 8:2, and then 50 μL Nafion binder and 950 μL isopropanol solvent were added to form a slurry after ultrasonic treatment. A certain volume of slurry was drawn with a pipette and dripped on a circular carbon paper with a diameter of 12 mm, and then placed in a vacuum oven for drying to prepare an electrode sheet.
[0056] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1 M LiBOB dissolved in TEGDME solution was used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0057] Example 13 Cobalt nitrate hexahydrate and ammonium molybdate heptahydrate were dissolved in 60 mL of deionized water at a molar ratio of 1:2, and hexadecyltrimethylammonium bromide was added, stirred for 30 min, transferred to a 100 mL reactor, and reacted for 50 min at a microwave power of 250 W. After the solution was cooled naturally, it was washed with water and ethanol three times each, then centrifuged to obtain a product, which was dried at 60 ° C. The product was sintered in a tubular furnace at a temperature of 500 ° C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0058] The precursor CoMoO4 and urea were mixed in a mass ratio of 1:3, sintered at 800 °C for 2 h in a N2 atmosphere, with a heating rate of 10 °C / min, and cooled naturally to room temperature. Molybdenum cobalt nitride was obtained. The above powder Co3Mo3N was mixed with carbon nanotube conductive glue in a mass ratio of 9:1, and then 50 μL Nafion binder and 950 μL isopropanol solvent were added to form a slurry after ultrasonic treatment. A certain volume of slurry was drawn with a pipette and dripped on a circular carbon paper with a diameter of 12 mm, and then placed in a vacuum oven for drying to prepare an electrode sheet.
[0059] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1 M LiTFSI dissolved in TEGDME solution was used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0060] Comparative Example 1 Cobalt nitrate hexahydrate and ammonium molybdate heptahydrate were dissolved in 60 mL of deionized water at a molar ratio of 1:2 and urea was added, stirred for 30 min, transferred to a 100 mL hydrothermal reactor, reacted at 100 °C for 18 h, and after the solution was naturally cooled, washed with water and ethanol 3 times each, then centrifuged to obtain the product, and dried at 60 °C. The product was sintered in a tubular furnace at a temperature of 500 °C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0061] The precursor CoMoO4 was sintered at 900 °C for 2 h in NH3 atmosphere, with a heating rate of 5 °C / min, and then cooled naturally to room temperature. Molybdenum cobalt nitride was obtained. The above powder Co3Mo3N was mixed with carbon nanotube conductive glue in a mass ratio of 8:1, and then 50 μL Nafion binder and 950 μL isopropanol solvent were added to form a slurry after ultrasonic treatment. A certain volume of slurry was drawn with a pipette and dripped on a circular carbon paper with a diameter of 12 mm, and then placed in a vacuum oven for drying to prepare an electrode sheet.
[0062] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, 1 M LITFSI / TEGDME was used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.
[0063] Comparative Example 2 Cobalt nitrate hexahydrate and ammonium molybdate heptahydrate were dissolved in 60 mL of deionized water at a molar ratio of 1:1 and urea was added, stirred for 30 min, transferred to a 100 mL hydrothermal reactor, reacted at 100 °C for 15 h, and after the solution was cooled naturally, washed with water and ethanol 3 times each, then centrifuged to obtain the product, and dried at 60 °C. The product was sintered in a tubular furnace at a temperature of 450 °C for 3 h, and ground to obtain a cobalt molybdate precursor.
[0064] The precursor CoMoO4 was sintered at 900 °C for 2 h in an NH3 atmosphere with a heating rate of 5 °C / min and then cooled naturally to room temperature to obtain molybdenum cobalt nitride.
[0065] The above powder Co3Mo3N was mixed with superconducting carbon black and PVDF in a mass ratio of 7:2:1, and then a proper amount of NMP solvent was added and ground into a slurry. The slurry was poured onto carbon paper and evenly coated with a scraper, and then dried in a vacuum oven to prepare an electrode sheet.
[0066] The prepared positive electrode sheet was used as the positive electrode of the battery, metallic lithium was used as the negative electrode of the battery, the glass fiber membrane was used as the battery separator, and 1.2 M LiTFSI dissolved in DMSO solution was used as the electrolyte. The CR2032 button battery was assembled in an argon-filled glove box. The above battery was subjected to electrochemical performance testing. All examples and comparative examples were tested at a constant current of 100 mAg -1 , the full discharge capacity at a cut-off voltage of 2 V and the -1 Constant capacity charge and discharge at current density up to 1000 mAhg -1 By testing the electrochemical properties of the materials in the examples and comparative examples, the results are as follows: As can be seen from Table 1, compared with the examples, the constant current discharge specific capacity of the positive electrode materials prepared in Comparative Examples 1 and 2 is relatively low, the limited capacity discharge voltage is relatively low, and the limited capacity charging voltage is relatively high, resulting in a low battery discharge capacity. This is because the precursor in the comparative example is synthesized by a hydrothermal method, and the precursor material is subsequently sintered at 900°C for 3 hours in an NH3 atmosphere, and the electrochemical reaction activity of the prepared material is relatively low. In the examples, microwave radiation heating is used, which is bulk heating, the reaction time is short, and the prepared precursor has a small particle size of nanometers. In Examples 7, 8 and 9, the subsequent sintering temperature is 450°C, which can well form a Co3Mo3N nanocrystalline structure, and the material exhibits good electrochemical reaction performance.
[0067] The 13 embodiments optimize and compare the power, time and other conditions for preparing the precursor by microwave heating, and consider the effects of the dispersant and the growth inducing agent on the precursor. Subsequently, the effects of the nitrogen source and the sintering system of the precursor on the Co3Mo3N nanocrystals are investigated. It can be seen that the microwave heating conditions, the dispersant and the growth inducing agent, the nitrogen source and the sintering system have a significant effect on the electrochemical reaction performance of the material.
[0068] Table 1 Electrochemical properties of Co3Mo3N cathode materials <![CDATA[Constant current discharge capacity (mAh g -1 )]]> Discharge voltage limit (V) Limiting charging voltage (V) Example 1 6260 2.54 4.35 Example 2 7755 2.61 4.32 Example 3 9050 2.65 4.29 Example 4 10112 2.44 4.47 Example 5 15025 2.71 4.34 Example 6 12503 2.77 4.37 Example 7 16576 2.86 4.26 Example 8 17232 2.84 4.22 Example 9 15500 2.86 4.33 Example 10 16401 2.85 4.25 Embodiment 11 14098 2.79 4.30 Example 12 13087 2.57 4.29 Embodiment 13 12062 2.55 4.34 Comparative Example 1 5592 2.47 4.43 Comparative Example 2 4620 2.49 4.46
Claims
1. A method for preparing molybdenum-cobalt nitride Co3Mo3N, characterized in that: The steps include: Step (1), synthesis of a nanorod-shaped cobalt molybdate precursor: a cobalt salt and a molybdenum salt in a certain molar ratio are mixed and dissolved in deionized water, and one of cetyltrimethylammonium bromide, urea or polyoxyethylene polyoxypropylene ether is added, and the mixture is stirred evenly and then transferred to a polytetrafluoroethylene reactor for microwave irradiation reaction. After the solution is cooled naturally, the mixture is washed with water and ethanol, and then centrifuged to obtain a product, which is then dried and pre-sintered to obtain a nanocrystalline cobalt molybdate precursor; Step (2), synthesis of bimetallic molybdenum-cobalt nitride with dual-effect catalytic effect: the obtained precursor and the nitrogen-containing compound are loaded into a porcelain boat according to a certain mass ratio, placed in a tubular furnace protected by an inert atmosphere, heated at a certain heating rate and kept warm for a certain time, and naturally cooled to room temperature to obtain the molybdenum-cobalt nitride.
2. The method for preparing a molybdenum-cobalt nitride Co3Mo3N according to claim 1, characterized in that: In step (1), the cobalt salt is one or two of ethylenediaminetetraacetic acid disodium cobalt salt, 4-cyclohexylbutyric acid cobalt salt, cobalt chloride, cobalt (III) acetylacetonate, hexamidocobalt (III) chloride, cobalt (II) fluoride or cobalt nitrate hexahydrate, and the mixing ratio is 1:9 to 9:1; the molybdenum salt is one or two of molybdenum (II) acetate dimer, bis (tert-butylimide) bis (dimethylamino) molybdenum (VI), trichloroisopropanol molybdenum (V), sodium molybdate dihydrate or ammonium molybdate heptahydrate, and the mixing ratio is 1:9 to 9:
1.
3. The method for preparing a molybdenum-cobalt nitride Co3Mo3N according to claim 1, characterized in that: In step (1), the molar ratio of the cobalt salt and the molybdenum salt in a certain molar ratio is 1:1-4:1, the stirring time is 0.5-2 hours, the microwave irradiation reaction uses a power range of 50-300 W, the reaction time is from 5 to 60 minutes, and the microwave reaction temperature is 100-200°C.
4. The method for preparing a molybdenum-cobalt nitride Co3Mo3N according to claim 1, characterized in that: In step (1), the centrifugal speed is 4000-10000 rpm, the time is 3-10 min, the drying temperature after centrifugation is 60-100° C., and the drying time is 12-24 hours; the product is sintered in a tubular furnace, the heating rate of the tubular furnace is 5-10° C. / min, the maximum temperature is 300-500° C., and the heating time is 2-3 hours.
5. The method for preparing molybdenum-cobalt nitride Co3Mo3N according to claim 1, characterized in that: The nitrogen-containing compound in step (2) is polypyrrole, melamine or urea; the mass ratio of the precursor to the nitrogen-containing compound is 1:1 to 1:
10.
6. The method for preparing molybdenum-cobalt nitride Co3Mo3N according to claim 1, characterized in that: The inert atmosphere described in step (2) is one or more of nitrogen, helium, argon or argon-hydrogen mixture; the heating rate of the tubular furnace is 2-10°C / min, the calcination temperature is 400-1000°C, and the calcination time is 1-6 hours.
7. A molybdenum-cobalt nitride Co3Mo3N, characterized in that: The method is prepared by any one of claims 1 to 6.
8. A lithium carbon dioxide battery, characterized in that: The molybdenum cobalt nitride Co3Mo3N described in claim 7 is mixed with a conductive agent and a binder in proportion, uniformly dispersed in NMP or isopropanol, and a conductive carbon paper is used as a current collector to prepare a lithium carbon dioxide battery positive electrode; metallic lithium is used as a negative electrode and a reference electrode; the electrolyte is prepared by dissolving a lithium salt in an organic solvent.
9. A lithium carbon dioxide battery as claimed in claim 8, characterized in that: The conductive agent used is one of superconductive carbon black, single-walled carbon nanotubes and multi-walled carbon nanotubes; the binder used is polyvinylidene fluoride or Nafion; the lithium salt concentration is 1 M to 1.2 M, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium dioxalate borate or lithium difluorooxalate borate, and the solvent used is tetraethylene glycol dimethyl ether or dimethyl sulfoxide.
10. Use of the molybdenum-cobalt nitride Co3Mo3N as claimed in claim 7 in a lithium carbon dioxide battery.
Citation Information
Patent Citations
Foam nickel loaded nanorod-like cobalt molybdate as well as preparation method and application thereof
CN108314092A
Preparation method and electrocatalysis application of nitrogen-doped CoMoO4 nanospheres
CN109718824A
Carbon-coated nickel-molybdenum nitride composite material and preparation method thereof
CN109926082A
Lithium carbon dioxide battery positive electrode catalyst and preparation method thereof
CN113206265A
Preparation method and application of bimetallic nitride multifunctional diaphragm
CN114649635A
Cited By
Cobalt nitride / molybdenum nitride electro-catalysis nanosheet, preparation method thereof and electrode plate
CN120485845A